Iron oxide polyaniline-coated nanoparticles modulate tumor microenvironment in breast cancer: an in vitro study on the reprogramming of tumor-associated macrophages - Camila Sales Nascimento; Naiara Clemente Tavares; Izabella Cristina Andrade Batista; Mônica Maria Magalhães Caetano; Eneida Santos de Oliveira; Stella Garcia Colombarolli; Anna Carolina Pinheiro Lage; Rodrigo Corrêa-Oliveira; Érica Alessandra Rocha Alves; Celso Pinto de Melo; Carlos Eduardo Calzavara-Silva (Cancer Nanotechnology, 2023)
Abstract Background Breast cancer is the neoplastic disease with the highest incidence and mortality in the female population worldwide. Treatment remains challenging due to various factors. Therefore, it is of great importance to develop new therapeutic strategies that promote the safe destruction of neoplastic cells without compromising patients' quality of life. Among advances in the treatment of breast cancer, immunotherapy stands out as a promising trend. Recent studies have demonstrated the potential of iron oxide nanoparticles in promoting the reprogramming of M2 macrophages (pro-tumor phenotype) into M1 macrophages (anti-tumor phenotype) within the tumor microenvironment, resulting in potent antitumor effects. In this study, the effect of polyaniline-coated iron oxide nanoparticles (Pani/y-Fe2O3) on macrophage polarization and breast cancer cell death was investigated. Methods The non-cytotoxic concentration of nanoparticles was determined using the MTT assay. For in vitro co-culture experiments, breast cancer cell lines MCF -7 and MDA-MB -231 and macrophages THP-1 were co-cultured in a Transwell system and then the effects of Pani/y-Fe2O3 on cell viability, gene expression, cytokine profile, and oxidative stress markers were investigated. Results The results showed that Pani/y-Fe2O3 nanoparticles induced M2-to-M1 macrophage polarization in both cell lines through different pathways. In MCF -7 and THP-1 macrophage co-culture, the study showed a decrease in cytokine levels IL -1β, upregulation of M1-associated genes (IL-12, TNF-α) in macrophages, resulting in increased MCF -7 cell death by apoptosis (caspase 3/7+). In MDA-MB -231 co-cultures, increases in cytokines IL -6, IL -1β, and oxidative stress markers were observed, as well as upregulation of the inducible nitric oxide synthase (iNOS) gene in macrophages, leading to tumor cell death via apoptosis-independent pathways (Sytox+). Conclusions These findings highlight the potential of Pani/y-Fe2O3 as a promising therapeutic approach in the context of breast cancer treatment by effectively reprogramming M2 macrophages into an anti-tumor M1 phenotype, Pani/y-Fe2O3 nanoparticles demonstrated the ability to elicit antitumor effects in both MCF-7 and MDA-MB-231 breast cancer cell lines.